2011
DOI: 10.1097/mcc.0b013e32834697bf
|View full text |Cite
|
Sign up to set email alerts
|

Advances in defibrillation

Abstract: The focus of these articles is to improve the delivery of defibrillation without interrupting chest compression and aiming to do so at an optimal stage of the resuscitation attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It may not be successful in many cases and it can induce arrhythmias or result in myocardial stunning. However, those are all acceptable risks because defibrillation is the most definitive therapy for patients presenting with cardiac arrest due to VF or VT. 20 Despite risks such as rib fractures, life-threatening complications from performing chest compressions are rare. 21 One study did suggest that chest compressions could cause the recurrence of VF after the first successful conversion in patients with out-of-hospital cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…It may not be successful in many cases and it can induce arrhythmias or result in myocardial stunning. However, those are all acceptable risks because defibrillation is the most definitive therapy for patients presenting with cardiac arrest due to VF or VT. 20 Despite risks such as rib fractures, life-threatening complications from performing chest compressions are rare. 21 One study did suggest that chest compressions could cause the recurrence of VF after the first successful conversion in patients with out-of-hospital cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that monophasic defibrillators usually require higher-energy shock than biphasic defibrillators. 8 With monophasic defibrillators, it was previously recommended to deliver up to three successive shocks if the first one was unsuccessful to decrease transthoracic impedance and therefore increase the amount of energy delivered to the myocardium with the second and the third shocks. 9 In a research setting the author determined in a few healthy dogs that a biphasic shock with an energy of 4 J/kg consistently terminated ventricular fibrillation, whereas an energy of 3 J/kg was less likely to be successful.…”
Section: Defibrillator-cardiovertermentioning
confidence: 99%
“…9 In a research setting the author determined in a few healthy dogs that a biphasic shock with an energy of 4 J/kg consistently terminated ventricular fibrillation, whereas an energy of 3 J/kg was less likely to be successful. 8 Open chest cardiac defibrillation is rarely indicated in veterinary patients unless ventricular fibrillation occurs in the operating room. It is usually suggested that the operator aim at using the lowest amount of energy possible.…”
Section: Defibrillator-cardiovertermentioning
confidence: 99%
See 1 more Smart Citation